2024
DOI: 10.3389/fpubh.2024.1197150
|View full text |Cite
|
Sign up to set email alerts
|

The role of education attainment on 24-hour movement behavior in emerging adults: evidence from a population-based study

Yanwei You,
Leiyu Mo,
Jing Tong
et al.

Abstract: PurposeThe purpose of this study was to explore the relationship between education level and health behavior including sleep, work activity, exercise activity, and sedentary behavior among emerging adults.MethodsThis study utilized data from the National Health and Nutrition Examination Survey (NHANES) collected between 2007 and 2018. The study sample included 4,484 emerging adults aged 18–25 years and the weighted participants were 30,057,813. Weighted multivariable regression analysis was performed to invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
(51 reference statements)
2
8
0
Order By: Relevance
“…Future studies may investigate hypertensive older adults with various subtypes of psychiatric history in order to construct distinct symptom networks. Forth, Previous researches have already demonstrated that sleep ( 57 , 58 ) and physical activity ( 59 , 60 ) are very important factors that have significant impacts on an individual’s physical and mental health. However, this study has not yet considered the effects of sleep and physical activity on mental disorders such as depression and anxiety in older adults with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may investigate hypertensive older adults with various subtypes of psychiatric history in order to construct distinct symptom networks. Forth, Previous researches have already demonstrated that sleep ( 57 , 58 ) and physical activity ( 59 , 60 ) are very important factors that have significant impacts on an individual’s physical and mental health. However, this study has not yet considered the effects of sleep and physical activity on mental disorders such as depression and anxiety in older adults with hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…We explored the relationship between the dietary intake of LMC foods, RPA, and SII using multivariable linear regression equations. Three discrete models were employed in the analytical framework [ 23 , 24 ]. Model 1 represented the unadjusted configuration, capturing the inherent relationship under examination.…”
Section: Methodsmentioning
confidence: 99%
“…This information was collected through interviews conducted by trained interviewers. During the survey, participants answered a question about their sleep hours routinely: “How much sleep do you get (hours) in a typical day?” 27 , 28 Referring to the suggestions by the National Sleep Foundation, 1 sleep duration was categorized into normal sleep (≥7 h), mild short sleep (≥6 h, <7 h), and severe short sleep (<6 h).…”
Section: Methodsmentioning
confidence: 99%